Factors affecting redox potential and differential sensitivity of SoxR to redox‐active compounds. Issue 5 (12th June 2015) - Lee, Kang‐Lok; Singh, Atul K.; Heo, Lim; Seok, Chaok; Roe, Jung‐Hye
Summary SoxR is a [2Fe‐2S]‐containing sensor‐regulator, which is activated through oxidation by redox‐active compounds (RACs). SoxRs show differential sensitivity to RACs, partly due to different redox potentials, such that Escherichia coli (Ec) SoxR with lower potential respond to broader range of RACs than Streptomyces coelicolor (Sc) SoxR. In S. coelicolor, the RACs that do not activate ScSoxR did not inhibit growth, suggesting that ScSoxR is tuned to respond to growth‐inhibitory RACs. Based on sequence comparison and mutation studies, two critical amino acids around the [2Fe‐2S] binding site were proposed as key determinants of sensitivity. ScSoxR‐like mutation (R127L/P131V) in EcSoxR changed its sensitivity profile as ScSoxR, whereas EcSoxR‐like mutation (L126R/V130P) in ScSoxR caused relaxed response. In accordance, the redox potentials of EcSoxRR127L/P131V and ScSoxRL126R/V130P were estimated to be −192 ± 8 mV and −273 ± 10 mV, respectively, approaching that of ScSoxR (−185 mV) and EcSoxR (−290 mV). Molecular dynamics simulations revealed that the R127L and P131V substitutions in EcSoxR caused more electropositive environment around [2Fe‐2S], making it harder to get oxidized. This reveals a mechanism to modulate redox‐potential in [Fe‐S]‐containing sensors by point mutations and to evolve a sensor with differential sensitivity to achieve optimal cellular physiology.